A rare case of Subretinal abscess secondary to Methicillin-Sensitive Staphylococcus aureus bacteremia - Elaine Ju Yen Gan; Jun Fai Yap; Sylves Patrick; Caroline Binson; Sheena Mary Alexander (Ocular Immunology and Inflammation, 2025)
Purpose: Subretinal abscess is a rare but vision-threatening manifestation of endogenous endophthal- mitis, accounting for approximately 5% of cases. It typically occurs in immunocompromised individuals and may be caused by a variety of microbial pathogens. We aim to highlight the importance of early recognition of subretinal abscess in a patient with preserved vision and minimal ocular symptoms. Methods: We report a case of acute subretinal abscess secondary to Methicillin-Sensitive Staphylococcus aureus bacteremia in a 55-year-old man with previously undiagnosed diabetes mellitus. The patient presented with floaters in the left eye one day after undergoing incision and drainage of a lip abscess. Results: Visual acuity remained 6/6 in both eyes. Fundus examination of the left eye revealed a superotemporal subretinal abscess with surrounding hemorrhage and Roth spots. Blood and pus cultures confirmed methicillin-sensitive Staphylococcus aureus. The patient was treated with a single dose of intravitreal vancomycin and ceftazidime, along with systemic antibiotics including intravenous cloxacillin, cefazolin, and oral ciprofloxacin. Pars plana vitrectomy was deemed unnecessary due to the lesion’s favorable location, size, and good presenting visual acuity. The lesion resolved with choroidor- etinal scarring, and vision was preserved. Conclusion: Subretinal abscess is an uncommon ocular complication of systemic infections that may be overlooked due to its subtle presentation. This case highlights the need for thorough ocular evaluation in patients with bacteremia, even in the presence of minimal visual symptoms. Early diagnosis and targeted antimicrobial therapy are crucial in preventing serious ocular morbidity and preserving vision.